1997
DOI: 10.1111/j.1399-3089.1997.tb00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the functional importance of the Gal epitope in an ex vivo model of xenotransplantation

Abstract: The galactose a 1‐3 galactose terminal disaccharide (Gal epitope) has been identified as the major porcine xenoantigen recognised by xenoantibody in human plasma. Elimination or suppression of the epitope or antibody will be a major factor in overcoming hyperacute rejection. Inhibition of the antibody by depletion or elimination of the epitope by gene knockout may reveal the importance of other xenoantibodies, and in addition elimination of the epitope may unmask or produce other xenoantibody combinations. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Like humans, Gal KO mice lack the αGal epitope [11]. Hearts from Gal KO mice function longer than control hearts when perfused ex vivo with human plasma [12], confirming along with other in vitro analyses [13, 14] the importance of αGal in HAR. However, a suitable in vivo model is necessary to study the role of anti‐αGal antibodies in DXR.…”
Section: Introductionmentioning
confidence: 59%
“…Like humans, Gal KO mice lack the αGal epitope [11]. Hearts from Gal KO mice function longer than control hearts when perfused ex vivo with human plasma [12], confirming along with other in vitro analyses [13, 14] the importance of αGal in HAR. However, a suitable in vivo model is necessary to study the role of anti‐αGal antibodies in DXR.…”
Section: Introductionmentioning
confidence: 59%
“…The aim of this study was to evaluate the effect of expressing HT or ST6Gal‐I on Sle x synthesis and E‐selectin adhesion. The strategy described here was drawn from xenotransplantation studies in which it has been shown by transfection or transgenic techniques, that HT reduces graft rejection between pig and man, by replacing the porcine xenoantigen Galα(1,3)Gal structures with the H(O) blood group Fucα(1,2)Gal [41–43]. Likewise, we addressed here the possibility that the synthesis of functional E‐selectin ligand sLe x , which requires the presence of α(2,3)‐linked sialic acid to be further fucosylated on its GlcNAc residue(s) by FucT‐VII [25], may be impaired after HT‐transfection.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of ␣Gal these strains develop low levels of anti-␣Gal antibody (which can be boosted to higher levels by exposure to ␣Gal-containing antigens) and are therefore proving invaluable in the investigation of this antigen-antibody system. The organs from ␣Gal-knockout mice, however, still appear to be susceptible to antibody-mediated rejection by ex vivo perfusion with human serum [23], suggesting that previously cryptic antigens have been exposed, against which humans also have natural antibody. The relevance of this observation with regard to potential ␣Gal-knockout pigs remains unknown.…”
Section: Modification Of Antigen Expressionmentioning
confidence: 99%